Repliek van het Rijksmuseum - Gosselink, Martine (BMGN - Low Countries Historical Review, 2014)
Response from the Rijksmuseum In its new format the Rijksmuseum is showing an integrated display of artistic and historical objects. As a result of its collection history, the museum focuses on Dutch art and history. Wherever possible the public is alerted to European and global contexts. Despite the first impression of the restored nineteenth century decoration schemes, the Rijksmuseum presents a twenty-first century, i.e. critical version of Dutch art and history. Limitations of the collection, which is evolving all the time thanks to new acquisitions, make it impossible to give all the topics noted by the critics their full due. Through texts and other means this shortcoming can be remedied to some extent. The Rijksmuseum is not a historical museum strictu sensu – and does not aim to be that either. Through collaborations with other historical museums, and with historians, the museum does aim to present historical knowledge to a large Dutch and international audience. Het Rijksmuseum heeft gekozen voor een geïntegreerde opstelling, waarin kunstvoorwerpen en historische objecten gezamenlijk worden getoond. Door de aard van de collectie van het Rijksmuseum vormen Nederlandse cultuur en geschiedenis de hoofdmoot. Waar mogelijk wordt de aandacht gevestigd op de Europese en mondiale context. Ondanks de eerste indruk van de gerestaureerde negentiendeeeuwse decoraties biedt het Rijksmuseum uitdrukkelijk een eenentwintigste-eeuws, dus kritisch beeld van de Nederlandse cultuur en geschiedenis. Beperkingen van de collectie, die overigens door middel van verwervingen wel steeds evolueert, maken dat niet aan alle door de recensenten gesignaleerde onderwerpen de door hen gewenste aandacht kan worden besteed. Door middel van tekstborden en andere hulpmiddelen wordt daarin ten dele voorzien. Het Rijksmuseum kan en wil niet een louter historisch museum zijn. Door middel van samenwerking met andere historische musea, en met wetenschappers, beoogt het museum historische kennis aan een omvangrijk Nederlands en internationaal publiek te presenteren.